모바일 애플리케이션 풍부성, 브랜드 인지도, 이용자 습관, 이용자 충성도 및 지속적 이용의도 간의 구조적 관계 - 김관현(Guan-Hyun Kim); 김유정(Yoo-Jung Kim); 윤종수(Jong-Soo Yoon) (韓國컴퓨터情報學會論文誌, 2013)
This study investigates the determinants of users' continuance intention in mobile application market, and examines the structural relationships between predictors and users' continuance intention. Based on the intensive review of prior research related to Internet and mobile services, mobile application richness, brand awareness, user habit, user loyalty were selected as the predictors of users' continuance intention. Using 259 surveys, the research model was assessed and the research hypotheses were tested. The findings show that mobile application richness is positively related with brand awareness and user loyalty. Brand awareness is proven to be a key predictor of user habit and user loyalty. Futhermore, it is shown that user habit has a direct impact on user loyalty and users' continuance intention. Finally, it was proven that user loyalty is a pretty important determinant of users' continuance intention. 본 연구의 목적은 모바일 애플리케이션 마켓 지속적 이용의도의 선행요인을 도출하고, 이들 선행요인들과 지속적 이용의도 간의 구조적 관계를 규명하고자 하는 것이다. 유선 인터넷 및 모바일 서비스와 관련된 기존 문헌을 심도 있게 검토하여 모바일 애플리케이션 풍부성, 브랜드 인지도, 이용자 습관 및 이용자 충성도를 지속적 이용의도의 선행요인으로 도출하였으며, 이들 선행요인들과 지속적 이용의도 간의 구조적 관계를 실증적 연구방법을 이용하여 검증하였다. 분석결과, 모바일 애플리케이션 풍부성은 브랜드 인지도와 이용자 충성도에 긍정적인 영향을 미치는 것으로 나타났다. 또한 브랜드 인지도는 이용자 습관과 이용자 충성도 형성에 중요한 역할을 하는 것으로 나타났으며, 이용자 습관은 이용자 충성도와 지속적 이용의도의 주요 결정요인으로 검증되었다. 마지막으로 이용자 충성도는 지속적 이용의도에 유의미한 수준에서 긍정적인 영향을 미치는 것으로 나타났다.